Contract farming in developing countries: Patterns, impact, and policy implications - Minot, Nicholas (Cornell University, 2007)
Contract farming may be defined as agricultural production carried out according to a prior agreement in which the farmer commits to producing a given product in a given manner and the buyer commits to purchasing it. Often, the buyer provides the farmer with technical assistance, seeds, fertilizer, and other inputs on credit and offers a guaranteed price for the output. Proponents of contract farming argue that it links small-scale farmers to lucrative markets and solves a number of problems small-scale farmers face in diversifying into high-value commodities. Opponents argue that the imbalance in power between the buyer (often a large agribusiness company) and the farmer leads to an agreement unfavorable to the farmer. Also, they argue that small farmers are often excluded from contract farming schemes, resulting in greater income inequality and social tensions in rural areas. To understand the rationale for contract farming, it is useful to view it as one form of vertical coordination, in between spot markets (in which supply and demand are coordinated through prices alone) and vertical integration (in which supply and demand are coordinated by having one firm carry out multiple stages in the market channel). Transaction cost economics, a branch of new institutional economics, suggests that, because contracting involves costs, it is economically justifiable only (1) when the buyer is a large firm (a processor, exporter, or supermarket chain); (2) when the product is characterized by large quality variations, perishability, technically difficult production, and/or a high value-bulk ratio; (3) when the destination market is willing to pay a premium for certain product or production attributes that can be ensured only by close coordination between farmers and buyers; and (4) when the policy environment is conducive. The vast majority of empirical studies suggest that contract farming schemes generally raise the income of farmers participating in the schemes. The evidence is less clear on the degree to which buyers are willing to contract with small-scale farmers—the answer depends on the commodity, the market, and the policy environment. Contract farming can be promoted with a favorable investment climate, deregulation of direct transactions between companies and farms, the development of grades and standards, facilitation of farmer organizations to link farmers and firms, cooperation with private firms on provision of extension services, provision of mediation services, and exploration of innovative ways to enforce contracts. Contract farming cannot serve as a broad-based strategy for rural development because it only makes economic sense for certain commodities in certain markets. On the other hand, in those circumstances, it can be an effective institution for helping small farmers raise their productivity and orient their production toward more remunerative commodities and markets. Your assignment is to recommend a set of policies to be considered by a developing-country government to facilitate contract farming for fruits and vegetables that will benefit low-income farmers, taking into account stakeholders’ interests.